The diversity and dry season habitat associations of fish communities in the Kabompo River Basin, Upper Zambezi, Zambia - Rennie, Craig Lawrence (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The Zambezian headwaters contain diverse fish communities which support thriving fisheries. This region and its fishes are under pressure from multiple anthropogenic threats, including overexploitation and large-scale developments with potential knock-on effects for the riparian communities. Previous studies have focused on known fisheries areas and the mainstem Zambezi River, neglecting large tributaries such as the Kabompo River. Consequently, little literature is available on the diversity and ecology of the fishes that inhabit these large tributaries, hindering the effective management and protection of biodiversity. This study aimed to fill the current knowledge gaps in the diversity and habitat associations of fish communities in the Upper Zambezi, using the Kabompo River as a case study. The first objective was to provide an updated checklist of the fishes of the Kabompo River basin using a compilation of historical data and field surveys. This study detailed the occurrence and distribution of 83 fish species within the Kabompo River basin. All these species have been recorded in the Upper Zambezi, with some of their ranges extending into the Middle (29 species) and Lower Zambezi (23 species) while others have more restricted distributions. The most diverse families were the Cyprinidae (26 species) and the Cichlidae (15 species). A number of potential undescribed species, whose taxonomic distinctiveness need further investigation were also collected. Taxonomic conflicts are also highlighted for some of the taxa that were previously considered to have broad geographic ranges or disjunct distributions. Consistent with findings from other studies within the region, the current taxonomy underestimates the diversity of fishes in the Kabompo River and Upper Zambezi. The second objective was to assess the habitat use of small-bodied fish communities during the low-flow period in 2019. Reconnaissance trips identified dominant mesohabitats along the middle Kabompo River around Jivundu. A total of 139 mesohabitats were sampled across the five dominant mesohabitats identified; Phragmites mauritianus, wood, rock, Vallisneria aethiopica and bare substrate. Catch per unit effort, species richness, Shannon diversity and Pielou's evenness differed significantly between these mesohabitats. Twenty-six species showed significant associations (p < 0.05) with a specific mesohabitat type or environmental variable (current velocity or depth). Eight species were associated with the woody habitat, with three of these, E. radiatus, E. unitaeniatus, and P. ngamensis being almost exclusively associated with this habitat. Enteromius kerstenii, E. lineomaculatus and S. depressirostris were almost exclusively associated with P. mauritianus and represent potential indicator species for this habitat. A number of species were also with both P. mauritianus and woody habitats. Nine species showed statistically significant associations with the rocky mesohabitat, with Amphilius uranoscopus and Petrocephalus longicapitis, being almost exclusive to rocky sections of the river. Therefore, species such as A. uranoscopus are potential indicators for monitoring the integrity of rocky habitats under threat from sedimentation. The strong associations indicate that this comprehensive baseline may be valuable indicators/ proxies for identifying anthropogenic induced change in the Kabompo basin. This would provide a basis to determine fish responses to regional environmental changes associated with human activities.
Keywords: Biodiversity -- Zambia -- Kabompo District; Ecology -- Zambia -- Kabompo District; Fish communities -- Zambia -- Kabompo District; Fishes -- Ecology -- Zambia -- Kabompo District; Freshwater habitats -- Zambia -- Kabompo District; Fishes -- Effect of human beings on -- Zambia -- Kabompo District; Fishes -- Climatic factors -- Zambia -- Kabompo District; Mesohabitat